Repeatability of bronchial hyperresponsiveness to adenosine-5'-monophosphate (AMP) by a short dosimeter protocol - De Meer, G (BMJ Group, 2001)
BACKGROUND—To study bronchial responsiveness to adenosine 5'-monophosphate (AMP) in population surveys, repeatability of a rapid dosimetric method with quadrupling doses was evaluated. METHODS—Volunteers with symptoms of airway respiratory allergy or asthma were invited for AMP challenges on two occasions. After each dose the fall in forced expiratory volume in one second (FEV(1)) compared with the post-saline value was determined. The cumulative doses of AMP needed to cause a fall in FEV(1) of 20% (PD(20)), 15% (PD(15)), and 10% (PD(10)) were calculated. Agreement was evaluated by means of kappa values. After excluding systematic differences in PD values on two occasions (t test), repeatability of a single estimation of the chosen PD values was calculated and expressed in doubling doses (DD). RESULTS—In 28 of 76 subjects a PD(20) was estimated on the two visits, in 29 subjects a PD(15) was estimated, and in 32 a PD(10) was obtained. Kappa values for a positive threshold were 0.89 for a cut off level for a 20% fall in FEV(1), 0.78 for a 15% fall in FEV(1), and 0.76 for a fall in FEV(1) of 10%. The PD values did not differ between the two visits and 95% repeatability of a single estimation was ±1.7 DD for PD(20), ±2.2 DD for PD(15), and ±2.4 DD for PD(10). The quadrupling dose method reduced time by 40% in non-hyperresponsive subjects and no adverse effects were observed. CONCLUSION—The short dosimeter protocol with quadrupling doses for AMP challenges is a rapid, reproducible tool for estimating bronchial responsiveness in population surveys.